Dialogue between Misa’ Kada Dipotuo, Pantan Kada Dipomate and the Third Sila of Pancasila: Exploring the Values of Unity and Harmony and Their Relevance to Indonesian’s Pluralistic Nation - Agustinus Abraham (Dewantara : Jurnal Pendidikan Sosial Humaniora, 2026)
This study examines the dialogue between the Torajan local wisdom misa’ kada dipotuo, pantan kada dipomate and the third principle of Pancasila, namely the Unity of Indonesia, in order to explore their shared values of solidarity, harmony, and national integration within the pluralistic context of Indonesia. While the principle of unity is often articulated normatively at the ideological level, its practical embodiment in everyday cultural life remains underexplored. Employing a qualitative design with a literature review approach, this study analyzes scholarly works, cultural practices, and socio-historical sources related to Torajan traditions and national values. The findings reveal that misa’ kada dipotuo, pantan kada dipomate functions as an ethical system that emphasizes kinship, mutual cooperation, collective responsibility, and communal solidarity, which are concretely manifested in rituals, communal labor, and deliberative forums. These lived practices provide a tangible foundation that grounds the abstract ideal of national unity. The dialogical integration of local wisdom and national ideology demonstrates that unity is most effective when rooted in cultural experience rather than solely in political discourse. This study contributes theoretically to interdisciplinary discussions on culture and nationalism and practically offers insights for character education and community development. Ultimately, strengthening Indonesia’s unity requires revitalizing local wisdom as a source of inclusive, participatory, and sustainable social harmony.